People-smart sustainable cities. - (:unkn) unknown (My University, 2020)
The 2030 Agenda for Sustainable Development and its Sustainable Development Goals (SDGs) provide an ambitious and comprehensive framework that opens new perspectives for policymaking and international cooperation. Its integrated character highlights the linkages and complementarities that exist between different goals and targets. UNECE is supporting countries to address these key sustainable development challenges through an integrated, multisectoral approach leveraging UNECE norms, standards and conventions, and by building capacities and providing policy assistance. At the crossroads of all UNECE programmes and expertise, four high-impact “nexus”areas have been identified where multiple SDGs converge: (a) Sustainable use of natural resources, (b) Sustainable and smart cities for all ages, (c) Sustainable mobility and smart connectivity, (d) Measuring and monitoring progress towards the SDGs. This publication is prepared within the “Sustainable and smart cities for all ages” nexus and advocates a “cities-based” approach to sustainable development. Cities are made of people, by people and for people. Sustainable measures will have to make sense to inhabitants of cities, making their life more liveable. Furthermore, it is people who drive sustainability and who are its ultimate source and beneficiaries. This vision underpins the notion of people-smart sustainable cities, introduced in this publication.
Keywords: Nachhaltige Stadtentwicklung; Nachhaltige Entwicklung; Umweltstandard; Nachhaltige Mobilität; Ressourcenschonung; Lebensqualität; Stadtbewohner; Sustainable Development Goals; Globaler Norden; Agenda 2030 für nachhaltige Entwicklung